If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -6 = 6x + -15 Reorder the terms: -6 + 7x = 6x + -15 Reorder the terms: -6 + 7x = -15 + 6x Solving -6 + 7x = -15 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -6 + 7x + -6x = -15 + 6x + -6x Combine like terms: 7x + -6x = 1x -6 + 1x = -15 + 6x + -6x Combine like terms: 6x + -6x = 0 -6 + 1x = -15 + 0 -6 + 1x = -15 Add '6' to each side of the equation. -6 + 6 + 1x = -15 + 6 Combine like terms: -6 + 6 = 0 0 + 1x = -15 + 6 1x = -15 + 6 Combine like terms: -15 + 6 = -9 1x = -9 Divide each side by '1'. x = -9 Simplifying x = -9
| -5(-12+3x)=-45 | | 36+x^2=-12 | | 40-3b=-b+6(3-4b) | | -2x^2-x-1=0 | | 3x^2-45+108=0 | | 2(3b-2)=3b+5 | | -s^2+4s-6=0 | | 11-4a=4 | | 8y+9=10+8y | | 14+3n=8n-3n-12 | | 5-2y+3+4y=8 | | -5(x+2)+8x=-2+3x-8 | | 9x-139=3x-13 | | -6(2+x)=4-8x | | (4x)=(x+120) | | 3(2x-7)-7(x-8)=x-7-6+4x | | (1+c^2)(4c^2+7c-3)=0 | | 15-(-4)=x | | 6(2x-9)=4+11x | | 18/7.5=x/5 | | 3x-y+z=1 | | -3x-5=6x-32 | | 13=2y-3y+4 | | 5x^2-10x-80=0 | | 2(w-3)=3(w-1) | | 7k^2-6k*3=3 | | 32/4=b+4/3 | | 80+6x=145+7x | | 8=8n-4(a+8) | | .125d+7=16 | | 16a^2+24a+9= | | 2x-3y+z=-3 |